O acoplamento plasmaron e a luminescência em semicondutores de gap direto - Costa Filho, Raimundo Nogueira da (1993)
The contribution of the electron-plasmon coupling to the photoluminescence spectrum of direct gap semicondutors is calculated. The photoexcited semicondutor is described as a coupled sistem of carriers and plasmons20. This coupled sistem of plasmons and electrons is used because it may influence the electron transport properties and its process of luminescence significantly. The photoluminescence spectrum is obtained using double-time Green's functions in the Zubarev13 approach. The coupled equations are solved self consistently within the random phase aproximation. The electron-plasmon coupling is responsible for a enhancement in the high energy side of the photoluminescence spectrum. It shifts towards lower energies when the photoexcited carriers temperature decreases, as was shown in some experimental results''' Similar results are obtained using Hamiltonians to describe electrons, holes and the coulomb interaction between them.